(untitled) (Raparin Journal of Humanities (RJH), 2024)
This study is concerned with the position and the importance of Jazeera region in Syriac texts by shedding light on the geographic border in Islamic sources and making a comparison with Syriac sources. The different names by Syriacs historians was according to their mind, the weight of the region has reflection in the Syriac sources and records. Undoubtedly, most of the Syriacs historians had lived in that region, and they were witnesses of the most events, which consists of political and religious events. All the changes which have been brought about in the region have had direct impact on representing the social condition. Most of the population of the region are Syriacs in the Syriac records and writings, that is why the Syriacs are considered as the original people of the region. In addition, the region has been pictured as a main center of Christian religion, Syriac language and culture, as most of the Syriacs historians were religious men, all of their writings were composed with religion. They show more religious conditions of the region in the Islamic authority framework, they refer to many names of the Christian Churches in the region.